Influence of water-stress acclimation and Tuber melanosporum mycorrhization on Quercus ilex seedlings (Agroforestry Systems, 2008)
Mycorrhizal and non-mycorrhizal holm oak (Quercus ilex L.) seedlings inoculated with black trufﬂe (Tuber melanosporum) were grown under nursery conditions and subjected to drought hardening for 4 months in autumn and winter followed by irrigation for 10 days. Leaf water potential and stomatal conductance were monitored during the 4 months of drought. When the test was completed (March), measurements were made for each treatment (inoculated or non-inoculated), and watering regime (watered and water-stressed). Pressure–volume curves, osmotic potential at full turgor, osmotic potential at zero turgor and the tissue modulus of elasticity near full turgor were calculated. Mycorrhizal colonization and growth, and the content of the main mineral nutrients N, P, K, Ca and Mg were measured. Water stress affected plant growth, caused an elastic adjustment of the plant tissues, and decreased the P and K content, and inoculation improved the nitrogen content. Drought acclimation apparently achieved the goal of improving the drought tolerance of holm oak seedlings, without depressing ectomycorrhizal root colonization by T. melanosporum.

Influence of water-stress acclimation and Tuber melanosporum mycorrhization on Quercus ilex seedlings - Domínguez Núñez, José Alfonso; Planelles González, Rosa; Rodríguez Barreal, José Antonio; Saiz de Omeñaca González, José Antonio (Agroforestry Systems, 2008)
Mycorrhizal and non-mycorrhizal holm oak (Quercus ilex L.) seedlings inoculated with black trufﬂe (Tuber melanosporum) were grown under nursery conditions and subjected to drought hardening for 4 months in autumn and winter followed by irrigation for 10 days. Leaf water potential and stomatal conductance were monitored during the 4 months of drought. When the test was completed (March), measurements were made for each treatment (inoculated or non-inoculated), and watering regime (watered and water-stressed). Pressure–volume curves, osmotic potential at full turgor, osmotic potential at zero turgor and the tissue modulus of elasticity near full turgor were calculated. Mycorrhizal colonization and growth, and the content of the main mineral nutrients N, P, K, Ca and Mg were measured. Water stress affected plant growth, caused an elastic adjustment of the plant tissues, and decreased the P and K content, and inoculation improved the nitrogen content. Drought acclimation apparently achieved the goal of improving the drought tolerance of holm oak seedlings, without depressing ectomycorrhizal root colonization by T. melanosporum.
Keywords: á mineral nutrition á; black truffle á drought; Black trufﬂe; Drought hardening; Elastic adjustment; elastic adjustment á inoculation; hardening á; Inoculation; Mineral nutrition; Nursery; nursery á osmotic adjustment; osmotic adjustment

The influence of mycorrhization with Tuber melanosporum in the afforestation of a Mediterranean site with Quercus ilex and Quercus faginea (Forest Ecology and Management, 2006)
A Holm oak (Quercus ilex L.) and Lusitanian oak (Quercus faginea) stand establishment, mycorrhizated with black trufﬂe (Tuber melanosporum Vitt.), situated in the north of Alicante, south-eastern Spain, was analyzed during the second year of plantation. The mycorrhization improved seedling growth, especially that of the shoots, encouraged water uptake of the seedlings during the summer drought, and improved total phosphorus absorption. Tuber melanosporum was found to colonize the roots of the seedlings very successfully